ANALYSIS OF POLICY IMPLEMENTATION SYSTEM PROGRAM FOR GIVING FE TABLETS TO ADOLESCENT WOMEN IN SCHOOL AS A PREVENTION EFFORT STUNTING IN TOBA DISTRICT THE YEAR 2023 - Purba, Leskarya; Rambey, Haris; Saputri, Ika Nur (JURNAL KESMAS DAN GIZI (JKG), 2023)
Stunting is a growth and development disorder in children due to critical malnutrition. Adolescence is a transition from childhood to adulthood which in its growth requires greater nutrition compared to other ages, especially iron. Adolescent health will determine the success of development in presenting a quality generation of the nation in the future. Adolescent girls are prospective mothers who will become pregnant and give birth, so efforts are made to obtain sufficient iron by administering Blood Supplement Tablets (TTD). This research is qualitative research with a phenomenological study design. This study displays a picture of a person's life experience when each individual subjectively feels the experience of a situation. The main informants were the nutrition manager at the health center, the teacher in charge of the UKS, and young female students who consumed iron supplement tablets. Triangulation informants are the Head of the Public Health Sector, the Nutrition Manager for the Health Service, the Promotion Manager for the Public Health Service, and the Head of the Health Center. The sample was determined using the Side Purposive technique, totaling 13 people. Competent human resources to facilitate and speed up the smooth running of the program. Facilities and infrastructure are in good condition and able to support program implementation. Planning, Actuating, and controlling went very well and clearly. The program coverage showed a decrease in the prevalence of stunting from the previous year of 26.92%. The program by giving Fe tablets to young women at schools in Toba Regency has succeeded in reducing the number of stunting cases.